The Reality of Racial Disparity in Criminal Justice: The Significance of Data Collection - Harris, David A. (2003)
Criminologists have long debated the presence of racial disparity at various places in the criminal justice system, from initial on-the-street encounters between citizens and police officers to the sentencing behavior of judges. What is new is the use of statistics designed to persuade the public, and not just other academics and researchers, that grave racial disparities exist in the system, and that these disparities necessitate significant policy changes